PERTUMBUHAN USAHA MIKRO KECIL DI KAWASAN WISATA PERMANDIAN AIR PANAS SULILI KABUPATEN PINRANG - Akhsan, Akhsan (Universitas Muhammadiyah Parepare, 2019)
This study has 3 objectives, namely to find out how much business, how much business capital and how much Micro Small Business income in the Sulili Hot Spring Tourism Area. The types of data used in this study are qualitative and quantitative data. This research uses descriptive research method. Data collection methods used are primary data, obtained through field observations and direct interviews. The data analysis technique used in this study is to use descriptive analysis. After going through the analysis process, the results are obtained that the Micro-Small Business in the Sulili Hot Spring Tourism Area did not experience an increase from 2011 to 2015, amounting to 20 MSEs. The minimum initial capital of MSEs is Rp. 250,000, and the highest is Rp.700,000. UMK income for the last 5 years is the lowest of Rp. 22,200,000 and high Rp. 45,600,000.